1987
DOI: 10.2337/diab.36.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Monoclonal Anti-L3T4 Antibody on Development of Diabetes in NOD Mice

Abstract: We analyzed the surface phenotypes of infiltrated cells in pancreases of nonobese diabetic (NOD) mice with monoclonal antibodies to mouse lymphocytes. Most of the infiltrated cells were Thy1+ and Ly1+ T-lymphocytes, and most of them were L3T4+ helper T-lymphocyte subsets. To elucidate the role of L3T4+ T-lymphocytes in the development of insulitis and diabetes in NOD mice, we treated the animals with injections of monoclonal anti-L3T4 antibody. Administration of this antibody prevented the insulitis and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…The disease is mediated by T cells because it can be prevented by treatment with anti-T-cell antibodies (Koike et al, 1987;Shizuru et al, 1988;Chatenoud et al, 1994), and can be transferred to prediabetic animals with T cells from diabetic mice (Wicker et al, 1986). Evidence is accumulating that T H 1 cells are responsible for autoimmunity in NOD mice and that endogenous T H 2 cells can protect mice against diabetes development to some degree (Debray-Sachs et al, 1991;Rabinovitch, 1993;Rapoport et al, 1993;Pennline et al, 1994;Gallichan et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…The disease is mediated by T cells because it can be prevented by treatment with anti-T-cell antibodies (Koike et al, 1987;Shizuru et al, 1988;Chatenoud et al, 1994), and can be transferred to prediabetic animals with T cells from diabetic mice (Wicker et al, 1986). Evidence is accumulating that T H 1 cells are responsible for autoimmunity in NOD mice and that endogenous T H 2 cells can protect mice against diabetes development to some degree (Debray-Sachs et al, 1991;Rabinovitch, 1993;Rapoport et al, 1993;Pennline et al, 1994;Gallichan et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Additionally the disease can be adoptively transferred into NOD neonates and irradiated young adult recipients by T cells (6,7), consisting of both CD4 + and CD8 + cell populations, from female diabetic mice (8). Further evidence comes from experiments involving the prevention of diabetes, which has been achieved after neonatal thymectomy (9), by the introduction of the nude gene (9) and by treatment of female NOD mice with either anti-CD4 or anti-class II monoclonal antibodies (10,11) or cyclosporin A (12).…”
mentioning
confidence: 99%
“…Previously it was shown that, like the BB rat (6), T-lymphocytes are necessary for the development of diabetes (7). More recently it was demonstrated that L3T4 + T-lymphocytes are necessary for the development of insulitis (8) and also for disease recurrence in allogeneic transplanted islets in these mice (9). Also, like the BB rat (10), one dose of cyclophosphamide (CY) can promote a progression to overt diabetes in NOD mice (11).…”
mentioning
confidence: 99%